Studi Komparasi Penerapan Strategi Numbered Heads Together (Nht) Dengan Index Card Match Terhadap Hasil Belajar IPA Siswa Kelas IV SD Muhammadiyah 3 Nusukan SurakartaTahun Ajaran 2015/2016 - Nur Hidayati, Dwi; , Drs. Saring Marsudi, SH. M.Pd (2016)
This research paper is aimed to determine: (1) The difference of science learning outcomes through the application strategy between Numbered Heads Together (NHT) and Incex Card Match toward science learning outcomes of IV grade students Muhammadiyah 3 Nusukan Surakarta Elementary School on year 2015/2016. (2) The better strategy toward science learning outcomes which obtained fromapplying Numbered Heads Together (NHT) and Index Card Match strategy. This research study categorized as quantitative research with an experimental model. The subject used to be analyzed is IV A and IV B grade students of Muhammadiyah 3 Nusukan Surakarta Elementary School. Technique of data collecting using test and documentary technique. Test instrument is used validity and reliability test. Technique of analyzing data using t-test with prerequisite test analysis in advance, namely normality test and homogeneity test. Based on analyzing data with with 5% signification standart derived from tcount > ttable , namely 2,146 > 2,002. And it isobtained the average score class between the class using Numbered Heads Together strategy and the class using Index Card Match strategy is 87,33 > 85,33. The conclusion of this research are: (1) This is a difference influence between Numbered Heads Together (NHT) and Index Card Match strategy toward science learning outcomes of IV grade students Muhammadiyah 3 Nusukan Surakarta Elementary School on year 2015/2016. (2) Numbered Heads Together (NHT) is better than Index Card Match strategy science learning outcomes of IV grade students Muhammadiyah 3 Nusukan Surakarta Elementary School on year 2015/2016. Keywords: Science Learning Outcomes, Strategy Numbered Heads Together (NHT),Strategy Index Card Match.